2005
DOI: 10.1051/0004-6361:20040388
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic study of the blazar S5 0716+714

Abstract: Abstract. We present the results of a multi-frequency study of the structural evolution of the VLBI jet in the BL Lac object 0716+714 over the last 10 years. We show VLBI images obtained at 5 GHz, 8.4 GHz, 15 GHz and 22 GHz. The milliarcsecond source structure is best described by a one-sided core-dominated jet of ∼10 mas length. Embedded jet components move superluminally with speeds ranging from 5 c to 16 c (assuming z = 0.3). Such fast superluminal motion is not typical of BL Lac objects, however it is stil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
116
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(137 citation statements)
references
References 44 publications
(74 reference statements)
15
116
6
Order By: Relevance
“…In addition, high bulk Lorentz factors of 16−21 were estimated based on the inferred jet speeds (Jorstad et al 2001). Radio maps from VLBI reveal a compact core-jet structure as has been suggested for BL Lacertae with different components moving at different velocities (Bach et al 2003). Jet speed > 11-15 h −1 c were estimated from the component proper motions Jorstad et al (2001), who also found quasi-periodic ejection of components every ∼ 0.7 yr. An analysis of the above 26 VLBI observations in 5-22 GHz frequency band gives an apparent velocity in range 5-10 h −1 c. Radio flux density and linear polarization light curves obtained from UMRAO at 4.8, 8.0, and 14.5 GHz were presented by Aller et al (1985) for the 1981-1984 period and those during 1985-1992 were studied by Wagner et al (1996).…”
Section: S5 0716+714mentioning
confidence: 86%
“…In addition, high bulk Lorentz factors of 16−21 were estimated based on the inferred jet speeds (Jorstad et al 2001). Radio maps from VLBI reveal a compact core-jet structure as has been suggested for BL Lacertae with different components moving at different velocities (Bach et al 2003). Jet speed > 11-15 h −1 c were estimated from the component proper motions Jorstad et al (2001), who also found quasi-periodic ejection of components every ∼ 0.7 yr. An analysis of the above 26 VLBI observations in 5-22 GHz frequency band gives an apparent velocity in range 5-10 h −1 c. Radio flux density and linear polarization light curves obtained from UMRAO at 4.8, 8.0, and 14.5 GHz were presented by Aller et al (1985) for the 1981-1984 period and those during 1985-1992 were studied by Wagner et al (1996).…”
Section: S5 0716+714mentioning
confidence: 86%
“…Figure 2 and the bottom panel in Fig. 4 demonstrate that, if the variability of S5 0716+714 is intrinsic and extends down to <32 GHz, the Doppler-boosting factor of the emission region must be much higher than the 20−30 suggested by Bach et al (2005). One possibility for enabling the Doppler factor to fall within this range is to increase the magnetic field strength and the electron density, as shown in Table 1.…”
Section: Discussionmentioning
confidence: 90%
“…Assuming H 0 = 70 km s −1 Mpc −1 , with Ω λ = 0.7, Ω M = 0.3, and Ω k = 0, and a redshift z > 0.3 based on the non-detection of a host galaxy (e.g. Wagner et al 1996), they derive a variability brightness temperature of T var > (2.1 ± 0.1) × 10 14 K. Bach et al (2005) analysed the data set of VLBI images of 11 jet components of S5 0716+714 at 4.9 GHz, 8.4 GHz, 15.3 GHz, and22.2 GHz, observed between 1992 and2001. Assuming that all the jet components move with the same speed along the jet (i.e. all components have the same bulk Lorentz factor), they propose that the observed wide range (from 5.5c to 16.1c) of apparent component speeds is due to variations in the viewing angle and limit the Lorentz factor and the viewing angle of the VLBI jet to Γ > 15 and θ < 2 • , respectively.…”
Section: The Bl Lac Object S5 0716+714mentioning
confidence: 97%
See 2 more Smart Citations